Scientific and Characteristic Dimension of 2013 Curriculum Implementation to Islamic Religious Education (PAI) Subject at SMKN 2 Bengkulu - Zubaedi Zubaedi (Jurnal Madania)
The article examines 2013 curriculum (K-13) implementation of Islamic Religious Education (PAI) subject towards paradigm of scientific and characteristic. There were two issues to be discussed: First, how do the teachers plan the K-13 implementation? Second, how do the teachers implement the learning patterns of PAI subject according to K13? Qualitative approach was employed by understanding related-person performance in certain situation naturally, or without influenced by surrounding. In qualitative study analysis, inductive method was applied by overlooking initial hypothesis, while exploring the patterns, forms, and themes in examining data systematically. The present study found that the implementation of K-13 in PAI subject at State Vocational High School (SMKN) 2 Bengkulu run systematically and programmatically. The K-13 program was began with conducting training, designing program for annually, every semester, monthly, and daily, as well as for remedial program. The learning process of K-13 was implemented through introductory, core, and closing activities. The K-13 implementation indicated scientific-based learning, such as inquiry, discovery, problem solving, and video analysis. This implementation revealed that benefit to build religious character.